Psychological and Physical Effects of Functional Training in Youth Volleyball Players a Quantitative Study - Xiaohui Jiang; Wen Sun; Jingli Yu (Revista de Psicología del Deporte (Journal of Sport Psychology), 2024)
In various athletic domains, including youth volleyball, the adoption of functional training has emerged as a potentially efficacious approach for enhancing athletic prowess and mitigating injury susceptibility. This quantitative inquiry delves into the psychological and physiological impacts of functional training on juvenile volleyball athletes. The study scrutinizes alterations in psychological constructs such as motivation and self-assurance, alongside physical parameters like muscular strength and agility, pre- and post-engagement with the training regimen. Employing a multi-phased methodology encompassing purposive sampling, questionnaire administration, physical evaluations, and quantitative statistical analyses, the research elucidates the efficacy of functional training in nurturing comprehensive athlete development. The findings underscore substantial enhancements in participants' psychological well-being and physical aptitude consequent to the intervention. By advocating for evidence-based training modalities tailored to the specific requisites of young volleyball athletes and bolstering their athletic achievement and welfare within the sport, this investigation constitutes a noteworthy contribution to the domain of sports science.